Analysis of the Unilever Compass Approach with the Concept of Sustainable Development - Yulia Puspita Dewi; Dwi Rahayu Nurmiati; Rafiq Hussain Ganaie (University of Muhammadiyah Malang, 2026)
The purpose of this article is to analyze how PT Unilever Indonesia's CSR program aligns with sustainability principles, viewed from the concepts of the sustainable development. Corporate Social Responsibility (CSR) has increasingly positioned corporations as important actors in promoting sustainable development by integrating economic, social, and environmental responsibilities into business strategies. In Indonesia, however, the integration of Sustainable Development Goals (SDGs) within corporate practices remains relatively limited. The Unilever Compass represents a sustainability-oriented framework designed to align corporate growth with broader social and environmental objectives. A Systematic Literature Review (SLR) method was employed to identify and analyze relevant academic literature and corporate reports. The review process resulted in 13 selected sources published between 2018 and 2024, which were examined using thematic analysis. The findings indicate that PT Unilever Indonesia implements an integrated CSR strategy covering climate action, waste reduction, health and well-being, equity and inclusion, and livelihood improvement. These initiatives demonstrate alignment with the three pillars of sustainable development. CSR practices also reflect a socio-ecological approach that strengthens stakeholder collaboration while simultaneously reinforcing corporate legitimacy within contemporary economic systems.